Nonprofit Vulnerability: An Exploratory Study - Watson, J.; Zhai, Linda; Gilchrist, David; Newby, R. (2016)
This mixed method study explores the symptoms and potential causes of nonprofit vulnerability within the Australian context. Following two focus groups with CEOs and Chairs of nonprofit organizations, an online survey was developed, pilot tested and distributed to nonprofit CEOs. Our findings suggest three symptoms that might be particularly useful in identifying nonprofit vulnerability: a substantial increase in unit costs/delivery hours; a substantial increase in the proportion of administration to program expenses; and a reduced ability to pursue the organization’s mission. The results also suggest various potential causes of nonprofit vulnerability, in particular: Board inadequacies; External environmental threats; Project management issues; and Funding constraints.